A meiotic mystery in experimental hybrids of the eastern mole vole (Ellobius tancrei, Mammalia, Rodentia) - V. G. Tambovtseva; S. N. Matveevsky; A. A. Kashintsova; A. V. Tretiakov; O. L. Kolomiets; I. Yu. Bakloushinskaya (Вавиловский журнал генетики и селекции)
Chromosomal rearrangements can lead to the formation of new stable karyotypes, nevertheless changing the architectonics of the nucleus. The differences in locations might promote Robertsonian (Rb) translocations and encourage meiotic drive in favour of changed chromosomes or against them. We hypothesized that hybridization and meiotic drive may produce new chromosomal forms in Ellobius tancrei. We crossed two forms with 2n = 50, and two pairs of different Rb metacentrics with partial (monobrachial) homology. In 10 years of inbred crossings (sister – brother), we got 9 generations of hybrids (262 litters, 578 animals). In the first hybrid generation, two trivalents, a tetravalent and 20 bivalents were revealed at meiotic prophase I. Hybrids of the first generation had lower fertility, fertility increased starting from the third generation. Instead of returning to parental karyotypes, starting from the second generation, hybrids obtained new chromosome sets, with different 2n (48, 49, 51, 52) and combinations of Rb metacentrics. Analysis of F4, F7 and F9 hybrids revealed that synapsis of homologous parts take place despite the presence of heterozygotes and monobrachial homology of Rb metacentrics. The most common meiotic disturbance was delayed synapsis, which resumed later compared to the homologous crossings. The late synaptic adjustments nevertheless provide a proper segregation of chromosomes and normal sets in the gametes. Therefore, some cells pass through meiosis successfully and promote viable gametes. We proved the hypothesis that origin of monobrachially homologous Rb translocations may lead to divergence in several generations, due to meiotic drive.